Incidence and risk factor of hemorrhagic cystitis after allogeneic transplantation with fludarabine, busulfan, and anti‐thymocyte globulin myeloablative conditioning. Issue 3 (17th April 2017) - Lam, Wilson; Storek, Jan; Li, Haocheng; Geddes, Michelle; Daly, Andrew
Abstract: Background: Hemorrhagic cystitis (HC) is a complication of allogeneic stem cell transplantation (SCT), associated with factors such as BK polyomavirus reactivation, age, conditioning regimen, and presence of graft‐versus‐host disease (GVHD). The incidence and impact of HC in patients receiving fludarabine (Flu), busulfan (Bu), and anti‐thymocyte globulin (ATG) conditioning is unknown. Methods: We conducted a case‐control study of patients undergoing SCT at our center between January 1, 2003 and Dec 31, 2012, to determine the incidence of HC and its effect on patient outcomes including overall survival (OS), relapse, non‐relapse mortality (NRM), GVHD, and healthcare resource use. Results: In total, 94 cases of HC were identified and matched to controls based on age, donor type, disease type, and disease status at transplantation. The total incidence of HC was 17.7% (117 of 661 patients). Cases had a higher rate (43.6% vs 27.1%, P =.0394) of acute GVHD (Grade II‐IV), and chronic GVHD requiring systemic steroids (34.9% vs 18.6%, P =.004). Male gender was found to be a risk factor (hazard ratio [HR]=1.725, P =.017). OS and progression‐free survival did not differ between cases and controls (OS HR=1.128, 95% confidence interval [CI] 0.7807‐1.639; progression‐free survival HR=0.8809, 95% CI 0.6320‐1.234), however the rate of NRM was higher in cases (HR=1.632, 95% CI 1.007‐2.830). Median length of hospitalization was longer for patients with HC than matched controls (65.5 days vs 40.5 days, P <.0001). Conclusion: HC is common in patients undergoing allogeneic SCT with FluBuATG conditioning, and affects the duration of hospitalization. Rate of GVHD is higher among patients with HC. While OS is not affected, an association was seen with higher NRM in our study. Improvement in treatment for HC may lead to reductions in morbidity and healthcare resource utilization.